2014
DOI: 10.1093/jxb/eru420
|View full text |Cite
|
Sign up to set email alerts
|

Tomato-Pseudomonas syringae interactions under elevated CO2 concentration: the role of stomata

Abstract: SummaryElevated CO2 enhanced defence against Pseudomonas syringae in tomato plants, not only by reducing stomata-mediated entry of P. syringae but also by invoking a stomata-independent pathway to counteract P. syringae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 45 publications
1
31
2
Order By: Relevance
“…CAs are important enzymes in CO 2 metabolism and we addressed whether they play a role in atmospheric CO 2affected plant disease resistance. Previous reports have shown that elevated CO 2 increased the disease resistance of tomato plants against Pst (Li et al 2014;Zhang et al 2015). In contrast, we found enhanced disease susceptibility to P. syringae and increased resistance against B. cinerea in Arabidopsis plants grown at increasing CO 2 levels ( Fig.…”
Section: Discussioncontrasting
confidence: 45%
“…CAs are important enzymes in CO 2 metabolism and we addressed whether they play a role in atmospheric CO 2affected plant disease resistance. Previous reports have shown that elevated CO 2 increased the disease resistance of tomato plants against Pst (Li et al 2014;Zhang et al 2015). In contrast, we found enhanced disease susceptibility to P. syringae and increased resistance against B. cinerea in Arabidopsis plants grown at increasing CO 2 levels ( Fig.…”
Section: Discussioncontrasting
confidence: 45%
“…This induction of stomatal closure is independent of ABA signaling (Montillet et al ., ). Based on these data and previous findings (Jin et al ., ; Li et al ., ), we conclude that CO 2 acts upstream of JA, and JA signaling is essential for stomatal closure under elevated CO 2 (Figure ).…”
Section: Discussionmentioning
confidence: 60%
“…The accumulation of H 2 O 2 in guard cells under elevated CO 2 was accompanied by an increase in NO accumulation in guard cells as well as upregulation of OST1 , NR and SLAC1 transcripts at both leaf and guard cell levels (Figs 2, 4, 5). As observed in a previous study (Li et al ., ), silencing NR abolished the elevated CO 2 ‐induced accumulation of NO in guard cells and stomatal closure. In this study, elevated CO 2 ‐induced stomatal closure could be blocked by either tungstate (an inhibitor of NR) or the NO scavenger cPTIO but not by L‐NAME/L‐NNA application (specific inhibitors of NO synthase) (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…S3). These results together indicated that the NR was primarily responsible for the NO production in guard cells under elevated CO 2 conditions as observed in our earlier study (Li et al ., ). Interestingly, the elevated CO 2 ‐induced NO accumulation in guard cells seems to acts downstream of H 2 O 2 induction, as silencing of RBOH1 almost completely blocked elevated CO 2 ‐induced NR activation and NO induction (Figs ).…”
Section: Discussionmentioning
confidence: 97%